IMPLEMENTASI KEBIJAKAN PERBUB TABALONG NO. 18 TAHUN 2021 (PERUBAHAN ATAS PERBUB TABALONG NO. 26 TAHUN 2020) DILIHAT DARI ASPEK KOMUNIKASI PADA KEGIATAN UMUM (PASAR) DI DESA KEMBANG KUNING KECAMATAN HARUAI KABUPATEN TABALONG (p3m.stiatabalong.ac.id, 2022)
Policy Implementation of Tabalong Regent Regulation No.18 of 2021 (Amendment to Tabalong District Regulation No. 26 of 2020) Seen from the aspect of communication in public activities (markets) in Kembang Kuning Village, Haruai subdistrict, Tabalong Regency, which is based on George C. Edward III Theory ( in Agustino, 2008: 150) which confirms that policy implementation with communication indicators consists of: Transmission, Clarity, Consistency. This study used a descriptive method with a quantitative approach, using questionnaire data collection techniques, observation and documentation. Data analysis used the percentage model developed by Muhammad Ali (1998: 184). Regent Regulation Number 26 of 2020 regarding guidelines for the implementation of the Corona Virus disease or Covid-19 health protocol as an effort to combat and find links to the Corona Virus. By providing understanding in order to prevent and break the chain of transmission of Covid-19 according to Tabalong Regent Regulation No. 26 of 2020 requires individuals and business entities, both legal entities and non-legal entities to implement health protocols. Such as wearing a mask, maintaining a minimum distance of 1 meter and washing hands with soap and running water. This regulation is based on presidential instructions in Regulation Number 6 of 2020 concerning improving health protocols in the prevention and control of Covid-19. The results of the research on Policy Implementation of Tabalong Regent Regulation No.18 of 2021 (Amendments to Perbub Tabalong No. 26 of 2020) Seen from the aspect of communication in public activities (markets) in Kembang Kuning Village, Haruai sub-disistrict, Tabalong Regency, it can be categorized as quite implemented. Keywords: Implementation, Aspects of Communication, General activitie (market)